Formulation and evaluation of an anti-epileptic drug-loaded microemulsion for nose to brain delivery - Kawtikwar, P S; Kulkarni, N P; Yadav, S; Sakarkar, D M (Asian Journal of Pharmaceutics (AJP), 2014)
The aim of the present study was to formulate an anti-epileptic drug-loaded microemulsion for nose-to-brain delivery.The oil system evaluated for the preparation of a stable microemulsion was iso-propyl myristate. A non-ionic surfactant likeTween 80 was used with polyethylene glycol 400 as a co-surfactant. A pseudoternary phase diagram for various proportions of Smix:oil was constructed by the water titration method. The effect of changing concentration of alcohol as a co-surfactantÂ  was also studied.The t-phase diagram shows that the water consumption capacity of the system was increased as the surfactant concentration was increased. It was also found that as the concentration of the alcohol was increased, the viscosity of the microemulsion decreased. After the identification of the microemulsion region, the composition of the microemulsion was fixed at oil 9-10%, Smix 35-40% and water 45-50%.The formulated microemulsion was evaluated for various parameters like pH, conductivity, zeta potential, viscosity and in vitro drug diffusion studies. All the evaluation parameters showed satisfactory results. Using this microemulsion, the solubility of valproic acid was increased from 1.29 to 36 mg/ml. Diffusion studies have shown a lag period of 45 min. Thirteen percent drug diffusion was achieved in 3 h. The prepared microemulsion was stable at 40Â°C and 75% relative humidity.